A Study of the Four Dhatus and Kammatthana Practice in Buddhism - Phrakru Sumetpatumaphon (Academic MCU Buriram Journal, 2021)
This research article has three objectives: 1) to study the meaning and importance of 4 Dhãtus, 2) to study the meaning and importance of meditation, and 3) to analyze the method of applying 4 Dhãtus to meditation practice in Buddhism. The research found that: 1. The meaning and significance of 4 Dhãtus refer to the determination or consideration of the four bases to see the truth. It means that the 4 Dhãtus are earth, water, wind, and fire. Whether any part is solid, such as hair, nails, teeth, that is the earth, what is permissive, that is the water, what is the condition of the body and glowing warmth that is the fire, the thing that moves the body is the wind. The importance of the four Dhãtus allows us to live. 2. Meaning and importance of meditation refer to the location of karma that is the work of the mind, what binds the mind not to be distracted, and calm. Meditation is considered to be the heart of Buddhism; the practice of meditation not only directly works for mental development but also contributes to physical development and personal development. Buddhism is characterized by solving all physical and mental problems. Dhatukammatthana considers the Dhatu as an emotion, that is, determines to consider the body as separate parts to see that it is only the four Dhatus, namely earth, water, fire, and air which are together. 3. Applying the 4 Dhatus in Buddhist meditation practice; (1) Pathavidhatu is classified as an earth element such as eyes, ears, nose, tongue, hair, fur, nails, teeth, etc., (2) Apodhatu is the liquid part. It is classified as water element such as blood, lymph, synovial fluid, snot, saliva, (3) Techodhatu is a hot element that gives warmth or strength to the body and does not warm the body, (4) Wayodhatu is a state of movement unique that moving or standing still, it is responsible for giving the ability to move to other elements that occur together, useful for social development, mental development and intellectual development. The application of the four Dhatus in Dharma practice, namely, in daily life, in eating, developing wisdom, contemplating the body, practicing Yonisomanasikara, contemplating breathing in and out, and death.